HUBUNGAN SECTIO CAESAREA DENGAN KEJADIAN ASFIKSIA DI RUMAH SAKIT UMUM DAERAH (RSUD) PRINGSEWU TAHUN 2014 - Maesaroh, Siti; Kurnia Utami, Etika (Jurnal Kelitbangan Bappeda Pringsewu, 2016)
The infant mortality rate is one indicator in determining the health status of children. Every year the death of the newborn or neonatal reached 37% of all deaths in children under five. According Dharmasetiawani in IDAI (2010), in Indonesia deaths due to asphyxia amounted to 41.94% (Basic Survey of Health Indonesia, 2012). To determine the relationship sectio caesarea with asphyxia at Regional General Hospital Pringsewu 2014. The study was cross sektional analytic approach. This research was conducted at the Regional General Hospital Pringsewu 2014. Subjects were Ms. Pringsewu maternity hospitals as much as 939 with a sample of 274 people using random sampling techniques. Means of collecting data in this study using a checklist sheet. Data were analyzed using chi-square test. The result showed that the number of cases of women giving birth with asphyxia in hospitals Pringsewu 2014 that 111 people (40.5%), the number of women giving birth in hospitals Pringsewu 2014 with sectio caesarea of 121 people (44.2%). There is a significant association between maternal maternity sectio caesarea with asphyxia in hospitals Pringsewu 2014. P value = 0.009. The results of this study concluded There is significant correlation between maternal maternity sectio caesarea with asphyxia in hospitals Pringsewu 2014. It is expected that the health workers to be able to disseminate the benefits of doing ANC routinely and regularly in a subsequent pregnancy and dissemination to the mother to keep conditions subsequent pregnancy in order to remain healthy and normal to prevent asphyxia.